The Junior Republic of William Reuben George (1866–1936) as an example of work with socially maladjusted young people in the United States - Kułan, Bartosz (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
This paper presents the assumptions put into practice by William Reuben George in the Junior Republic in the State of New York. The person of the founder of this pedagogical solution has not yet been widely known in Polish literature. The assumptions introduced in the Junior Republic were part of the so-called progressive approach in working with juvenile offenders in the United States. The paper presents the main assumptions used in working with young people, the idea of the Junior Republic and the daily activities of minors. The paper is concluded with a summary.